Screening phytochimique et caractérisation par chromatographie sur couche mince CCM des extraits des feuilles de Moringa oleifera - REZGUI, MOHAMED AYMENE; CHENTOUF, YACINE (My University, 2020)
Moringa Oleifera is considered to be one of the most useful trees in the world, as almost any part of the Moringa tree can be used for food, medicine and industrial purposes. With the aim of knowing the biological activities of medicinal plants traditionally used by the population, our work focused on the study of raw extracts of Moringa Oleifera leaves by the method of infusion and methanolic maceration. The phytochemical screening revealed a wealth of bioactive substances. The characterization of alkaloids and flavonoids on TLC plaques revealed a large number of spots, indicating a significant richness of compounds of these secondary metabolists
Keywords: Moringa Oleifera; phytochemical screening; CCM.